2009
DOI: 10.1007/s11240-009-9496-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid production in callus and cell suspension cultures of Buddleja cordata Kunth

Abstract: Plant tissue cultures represent a potential source for producing secondary metabolites. In this work, Buddleja cordata tissue cultures were established in order to produce phenylpropanoids (verbascoside, linarin and hydroxycinnamic acids), as these metabolites are credited with therapeutic properties. Highest callus induction (76.4-84.3%) was obtained in five treatments containing 2,4-Dichlorophenoxyacetic acid (2,4-D: 0.45-9.05 lM) with Kinetin (KIN: 2.32, 4.65 lM), whereas highest root induction (79.6%) corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 22 publications
(37 reference statements)
3
42
1
10
Order By: Relevance
“…The maximum content of acteoside (about 14.25 lg/g cell fresh weight) was observed on the 17th day of cultivation cycle. These results are in agreement with earlier studies (Estrada-Zúñiga et al 2009;Nezbedová et al 1999), that reported acteoside production increased parallel to cell growth, and reached a maximum several days after maximum cell growth. In addition, Ouyang et al (2005) demonstrated at the end of lag phase the cells of Cistanche deserticola started to grow rapidly and the biosynthesis of PeG was activated.…”
Section: Dynamics Of Acteoside Production In Suspension Culturesupporting
confidence: 94%
See 3 more Smart Citations
“…The maximum content of acteoside (about 14.25 lg/g cell fresh weight) was observed on the 17th day of cultivation cycle. These results are in agreement with earlier studies (Estrada-Zúñiga et al 2009;Nezbedová et al 1999), that reported acteoside production increased parallel to cell growth, and reached a maximum several days after maximum cell growth. In addition, Ouyang et al (2005) demonstrated at the end of lag phase the cells of Cistanche deserticola started to grow rapidly and the biosynthesis of PeG was activated.…”
Section: Dynamics Of Acteoside Production In Suspension Culturesupporting
confidence: 94%
“…Production of acteoside has been reported in cell suspension cultures (Chen et al 2007;Estrada-Zúñiga et al 2009;Saimaru and Orihara 2010). Higher acteoside production was reported in suspension cultures than in the callus of Aphelandra sp.…”
Section: Dynamics Of Acteoside Production In Suspension Culturementioning
confidence: 94%
See 2 more Smart Citations
“…In many other plant species callus cultures were reported to be a good source of verbascoside. For example, Estrada-Zúñiga et al (2009) found that callus culture of Buddleja cordata produced 86 mg g -1 DW of verbascoside, compared to 10 and 68 mg g -1 DW in the leaves and roots of the wild plants, respectively. Inagaki et al (1991) reported the production of the compound in callus cultures cultivated on MS medium with different concentrations of an auxin-2,4-D in ten various plant species including of R. glutinosa.…”
Section: Production Of Phenylethanoid Glycosidesmentioning
confidence: 99%